Sensibilidade à encefalopatia associada à sepse: comparação entre animais sedentários e não sedentários - Rodrigues, Judite Filgueiras (2017)
Sepsis is characterized by physiological abnormalities arising from an infectious and inflammatory response. During sepsis, the central nervous system (CNS) is rapidly affected, resulting in sepsis-associated encephalopathy (SAE). Studies demonstrate the relevance of physical exercise as an intervention to improve the cognitive function and health of the CNS, in view of its effects on neurogenesis and neuroplasticity. Thus, this study aimed at comparing the sensitivity to SAE under neuroinflammatory and neurochemical parameters in sedentary rats and rats submitted to aerobic physical conditioning. Adult male Wistar rats were randomly assigned to the sham+ Sedentary (S) (n = 7), sham+ Trained (T) (n = 7), cecal ligation and perforation (CLP)+S (n = 10) and CLP+T (n = 10) and subjected to treadmill training for 21 days. Twenty-four hours after the last training session, the animals were submitted to sepsis induction by the CLP model. Forty-eight hours later the animals suffered assisted painless death by thiopental overdose followed by guillotine decaptation and the prefrontal cortex was harvested to determine the levels of TNF-α, IL-6 and IL-10 , neutrophil infiltrate, oxidative damage to lipids and proteins and antioxidant enzymes SOD and CAT. Sepsis increased the levels of TNF-α, IL-6 and neutrophil infiltrate, as well as damage to lipids and carbonylated proteins, while reduced IL-10 levels, the integrity of sulfhydryl groups and the activity of SOD and CAT. Aerobic physical conditioning prevented the increase of TNF-α, reduced neutrophil infiltrate and the damage to lipids and sulfhydryl groups, while increased SOD and CAT activity. In conclusion, aerobic physical conditioning exerted positive effects on neuroinflammatory and neurochemical parameters in the prefrontal cortex of rats with polymicrobial sepsis. Keywords: sepsis, brain dysfunction, oxidative stress, sedentarism, physical exercise.